2016
DOI: 10.1002/da.22579
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder associated with unexpected death of a loved one: Cross-national findings from the world mental health surveys

Abstract: Background Unexpected death of a loved one (UD) is the most commonly reported traumatic experience in cross-national surveys. However, much remains to be learned about PTSD after this experience. The WHO World Mental Health (WMH) Survey Initiative provides a unique opportunity to address these issues. Methods Data from 19 WMH surveys (n=78,023; 70.1% weighted response rate) were collated. Potential predictors of PTSD (respondent socio-demographics, characteristics of the death, history of prior trauma exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 43 publications
4
30
0
Order By: Relevance
“…For example, a large prospective study of victims of Hurricane Katrina found that socio-economic status was a significant predictor of speed of PTSD recovery after that natural disaster (McLaughlin et al, 2011). Previous research on the predictors of recovery in trauma-specific samples have focused largely on trauma characteristics and prior psychopathology (Atwoli et al, 2017; Bromet et al, 2017; Stein et al, 2016), neither of which was considered in the aggregate WMH analyses due to the small numbers of cases associated with each trauma type.…”
Section: Resultsmentioning
confidence: 99%
“…For example, a large prospective study of victims of Hurricane Katrina found that socio-economic status was a significant predictor of speed of PTSD recovery after that natural disaster (McLaughlin et al, 2011). Previous research on the predictors of recovery in trauma-specific samples have focused largely on trauma characteristics and prior psychopathology (Atwoli et al, 2017; Bromet et al, 2017; Stein et al, 2016), neither of which was considered in the aggregate WMH analyses due to the small numbers of cases associated with each trauma type.…”
Section: Resultsmentioning
confidence: 99%
“…A dichotomous variable "sample" representing in which study the participant was included (i.e., Study 1 or Study 2), was included as covariate by regressing each construct at both time points onto this variable. To explore whether type of loss (expected vs. unexpected) influenced the findings (given that an unexpected loss is a correlate of PTSD; Atwoli et al, 2017), we ran a second round of analyses, but now only including people who had experienced an unexpected loss (n = 215). A maximum likelihood estimator was used.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The disorder develops after exposure to a traumatic event (e.g., traffic collisions, terrorist attacks, physical violence, unexpected death of a loved one, etc.) and is accompanied by poor fear extinction in the long term (Al‐Hadethe, Hunt, Thomas, & Al‐Qaysi, ; Atwoli et al, ). Currently, the exact pathogenesis of PTSD is not fully elucidated despite the presence of extensive research in animals and humans.…”
Section: Introductionmentioning
confidence: 99%